To Come Out or Not to Come Out: Queer Coming Out in Nine Lives by Zodwa Nyoni - Emre Ozmen (Theatre Academy)
Queer studies, as a field of gender studies with particular focus on LGBTQ+ culture and issues at the end of the twentieth century, has increased nonbinary individuals’ visibility. Because it has enabled queer people to define and reveal their non-normative gender identities and sexual preferences in many ways and platforms. This process, also called “coming out”, has become one of the watersheds in a queer person’s life. Despite its importance for the queer individuals, this process is a rather manifold one. Variables such as race, religion, and family cause difficulties in terms of the coming out process of individuals. In 2014, Zimbabwean playwright Zodwa Nyoni wrote Nine Lives which delves into the coming out process and its challenges. The play portrays Ishmael’s experiences who flees from his country Zimbabwe due to his sexual identity. Although he succeeds entering the United Kingdom, Ishmael continues to struggle to be out with his sexual preferences. This paper scrutinises the process of coming out and how the internal and external factors in a queer person’s life affect the process and its outcome as they are manifested in Nine Lives.